STUDIES ON THE MECHANICAL PRESSING CONDITIONS IN RUBBER SEED OIL (Hevea brasiliensis) PRODUCTION FOR LEATHER TANNING - Ono Suparno, Kurnia Sofyan dan Muh. Idham Aliem (Jurnal Teknologi Industri Pertanian, 2010)
ABSTRACT  Pressing is one of the important steps in the oil production by using a mechanical method.  Optimization in the oil pressing need is conducted in order to obtain high yield and quality of the oil. A suitable temperature and pressure in the oil pressing will give an optimum condition for the operation causing oil flows easier.  The objectives of this research were to get conditions of temperature and pressure in rubber seed pressing in order to obtain high yield and physico-chemical properties of rubber seed oil for the chamois tanning.  The sun-dried seeds were dried in an oven at temperature of 70 oC for one hour, and then were pressed by using a hydraulic pressing at temperatures of 55 oC, 65 oC and 75 oC and pressures of 15 tonnes/196.15 cm2, 17.5 tonnes/196.15 cm2 and 20 tonnes/196.15 cm2.  Yield of the oil and oil content of its cake were measured.  Their physico-chemical properties of the oil including colour, iodine value, acid value, and free-fatty acid content were measured.  The results show that condition giving the best yield and physico-chemical properties of the rubber seed oil for leather tanning was pressing at temperature of 75 oC and pressure of 20 tonnes/196.15 cm2.     Keywords:  rubber seed oil, pressure, temperature, yield, leather tanning